Micropatterned ultrathin MOF membranes with enhanced molecular sieving property - Kang,H; Wang,B; Guo,S; Li,K (Angewandte Chemie International Edition, 2018)
Metal–organic frameworks (MOFs) are attractive crystalline materials for membranes due to their diverse crystalline pore structures and molecular separation properties. However, the fabrication cost is relatively high compared to conventional polymeric membranes. The concern of the cost could be eased if they are part of a valueadded device, for example, as the key separation unit in a labonachip device. This study demonstrates the feasibility of miniaturization of MOF membranes by patterning the membrane surface, a necessary step for MOF membranes to be used in compact devices. Waterstable ultrathin UiO66 membranes with a thickness down to 250nm on a substrate with a complex pattern were grown. The patterned membranes showed a 100 % improvement in the apparent permeation flux over conventional flatUiO66 membranes without compromising the molecular separation property, indicating the complexity of a surface would not be a formidable obstacle to the MOF membrane fabrication.